Analisis Risiko Operasional pada UMKM Pabrik "Sri Tahu" di Watukebo Kecamatan Ambulu - Laella Wardiah; Eko Budi Satoto; Yohanes Gunawan Wibowo (BUDGETING : Journal of Business, Management and Accounting, 2023)
The research was conducted with the aim of knowing the management of the "Sri Tahu" factory MSME in internal risk, human resource risk, external risk, and raw material risk. The method used is descriptive qualitative using purposive sampling method. The sample in this study was 6 people who were the population of "Sri Tahu" factory employees. Based on the research results in risk analysis with Enterprise Risk Management, there are 20 risks which include internal risk, external risk, human resource risk, and raw material risk. There is a risk response, namely at the extreme,high, moderate and low level. From the calculation of risk scoring, the highest risks are extreme risk and high risk. Some of the risks included in the extreme risk are hot steam from burning stoves, unhygienic environment, wood dust from stove burning activities, fluctuating soybean raw material prices, errors in recording financial reports, lack of quality control of products to be marketed, accidents Work. While high risk, namely damage to machinery and equipment in the production process, production failure, fire, poor OSH system, damaged raw materials, destruction of tofu during cutting, imperfect clumping process. Keywords : External Risk, Human Resource Risk, Internal Risk, Raw Material Risk.